English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

4 answers

Question 1
(3 + 2) ³
= 5 ³
= 125
Question 2
(2 x 3) - (3 x -2 )
= 6 + 6
= 12

2007-10-06 11:09:16 · answer #1 · answered by Como 7 · 1 0

2.=12

2007-10-06 13:02:49 · answer #2 · answered by wrencabin 2 · 0 0

Question 1.
First plug in the numbers for x and y, once you do that it becomes: ( 3 - -2)^3. Remember that two negatives make a positive so it becomes: (3 + 2)^3, so then it becomes (5)^3, which equals 5x5x5, which equals 125.

Question 2.
First plug in the numbers for x and y, once you do that it becomes: 2(3) - 3(-2). Then you multiply the numbers and it becomes 6+6, which equals 12.

Was there anything you didn't understand?

2007-10-06 13:20:31 · answer #3 · answered by Anonymous · 0 0

1. [3 -(-2)] = [3 + 5] = 8
8^3 = 8 x 8 x 8 = 64 x 8 = 512

2. 2x - 3y
2 (3) - 3[-2] =
6 + 6 = 12

2007-10-06 13:09:48 · answer #4 · answered by duffy 4 · 0 0

fedest.com, questions and answers